2013
DOI: 10.1111/ans.12360
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography in acute abdominal pain: an overused investigation?

Abstract: Abdominal CT scans frequently changed the clinical diagnosis and patient disposition. Twenty-three per cent of patients had no identifiable cause on CT scan for their acute abdominal pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The study analyzed the concordances between pre-CT, post-CT and final diagnoses of 834 medical records of patients with AAP, in search for situations where CT might be considered unnecessary. Of the total, 108 (12.9%) CT scans with normal results were found and 231 (27.7%) were considered unspecific for AAP, which is lower than the frequency reported in the literature 14 but in agreement with those reported for the final diagnosis of NSAP 20,21 .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The study analyzed the concordances between pre-CT, post-CT and final diagnoses of 834 medical records of patients with AAP, in search for situations where CT might be considered unnecessary. Of the total, 108 (12.9%) CT scans with normal results were found and 231 (27.7%) were considered unspecific for AAP, which is lower than the frequency reported in the literature 14 but in agreement with those reported for the final diagnosis of NSAP 20,21 .…”
Section: Discussionsupporting
confidence: 57%
“…According to the organization, 73% of US physicians admit that the frequency with which diagnostic tests or medical procedures are requested is a serious health care problem 13 . Systermans et al (2014) warn that, while abdominal CT correctly shows disease in 92-97% of patients, CT scans show normal results in 44% of patients and correspond to clinical data in 70% of cases. Thus, the authors even questioned whether CT scans might have decreased clinical skills or whether physicians' poor confidence in their capacity to evaluate patients with acute conditions led to the replacement of traditional physical examination by modern imaging techniques 14 .…”
Section: Introductionmentioning
confidence: 98%
“…The reason why CT scan facilitated patient disposition might be that it shortened the diagnostic process. 13 14 Systermans et al 11 reported that abdominal CT scans frequently changed the clinical diagnosis and patient disposition. In addition, they reported that the rate of pulmonary embolism diagnosis in the ED increased significantly along with the increased availability and use of CT. 9 Hoffmann et al 19 suggested that early coronary CT angiography might significantly improve patient management in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the proportion of ED visits with a diagnosis of pulmonary embolism has increased significantly, and this rise can be attributed in large part to the increased availability and use of CT. 9 Ng et al 10 reported that early abdominopelvic CT for acute abdominal pain may reduce mortality. Systermans et al 11 suggested that abdominal CT scans frequently resulted in a change in the clinical diagnosis and patient disposition. Kocher et al 12 stated that the increased use of CT in the ED was associated with a decline in admissions and transfers.…”
Section: Introductionmentioning
confidence: 99%
“…The study analyzed the concordances between pre-CT, post-CT and final diagnoses of 834 medical records of patients with AAP, in search for situations where CT might be considered unnecessary. Of the total, 108 (12.9%) CT scans with normal results were found and 231 (27.7%) were considered unspecific for AAP, which is lower than the frequency reported in the literature 14 The analysis was directed to diagnoses of NSAP, OU and AP, which together account for more than 70% of the final diagnoses. As broadly reported in other studies, the CT showed a high degree of accuracy [1][2][3][4][5] , with a moderate correlation between clinical, post-CT and final diagnoses for NSAP and OU and excellent for AP.…”
Section: Discussionmentioning
confidence: 99%